2001
DOI: 10.1080/20014091111956
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Hormesis: Data and Interpretations

Abstract: Although the biological effects of large doses of ionizing radiation are predominantly harmful, low-to-intermediate doses have been observed to enhance growth and survival, augment the immune response, and increase resistance to the mutagenic and clastogenic effects of further irradiation in plants, bacteria, insects, and mammals. The existence of these stimulatory, or "adaptive", responses implies that the dose-response relationships for genetic and carcinogenic effects of radiation may be similarly biphasic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 64 publications
0
37
0
1
Order By: Relevance
“…of astronauts during long-term space flights, risk assessment and management, and cancer treatment strategies (Delone et al, 1991;Wang and Cai, 2000;Upton, 2001;Takahashi et al, 2002;Bonner, 2003;Mortazavi et al, 2003aMortazavi et al, , 2003bLiu, 2003;Schaffer et al, 2004;Preston, 2005). In preliminary cytogenetic studies, after in vitro irradiation with a test dose of gamma rays, a strong cytogenetic AR was induced in the lymphocytes of residents of the very high background radiation areas of Ramsar (Ghiassi-nejad et al, 2002).…”
Section: Relevance Of the Adaptive Responsementioning
confidence: 99%
See 1 more Smart Citation
“…of astronauts during long-term space flights, risk assessment and management, and cancer treatment strategies (Delone et al, 1991;Wang and Cai, 2000;Upton, 2001;Takahashi et al, 2002;Bonner, 2003;Mortazavi et al, 2003aMortazavi et al, , 2003bLiu, 2003;Schaffer et al, 2004;Preston, 2005). In preliminary cytogenetic studies, after in vitro irradiation with a test dose of gamma rays, a strong cytogenetic AR was induced in the lymphocytes of residents of the very high background radiation areas of Ramsar (Ghiassi-nejad et al, 2002).…”
Section: Relevance Of the Adaptive Responsementioning
confidence: 99%
“…adaptive protection causing DNA damage prevention and repair and immune stimulation (Upton , 2001;Liu, 2003;Ghiassi-nejad et al, 2004;Feinendegen, 2005). Low to intermediate doses of ionizing radiation have been observed to enhance growth and survival, augment the immune response, and increase resistance to the mutagenic and clastogenic effects of further irradiation in plants, bacteria, insects and mammals (Upton, 2001).…”
Section: Relevance Of the Adaptive Responsementioning
confidence: 99%
“…10 And reduction of ROS by antioxidants can shorten life span. 10,53 It has even been suggested that the beneficial effects of physical exercise are partly based on the ROS generating capability of exercise. 10 If induction of ROS prolongs life span (by whatever mechanism), then ROS simply cannot be a cause of aging.…”
Section: Paradoxical Effects Of Ros: Hormesismentioning
confidence: 99%
“…Risk estimates at or below these levels are difficult to obtain directly from epidemiological data (8) and are based, at least partly, on linear extrapolations from existing high-dose data (9)(10)(11). However, the validity of this assumption is challenged by some radiobiological phenomena, such as the bystander effect, low-dose hypersensitivity, delayed genomic instability, and induced DNA repair, which are difficult to reconcile with a linear no-threshold hypothesis based on mechanistic considerations (12)(13)(14)(15)(16)(17). Because these effects have yet been demonstrated only in cell culture systems or, at best, in animal models, their in vivo significance for people has remained unclear.…”
mentioning
confidence: 99%